Avaliação espectrofotométrica da estabilidade de cor de materiais restauradores estéticos - Samra, Adriana Postiglione Bührer (2004)
Color match is one of the most important characteristics of the aesthetics restorative materials. Color stability is a demanding characteristic of the restorative material as though as it indicates its chemical stability. The purpose of this research is to verify the color stability of five aesthetic restorative materials when immersed in coffee solution and the efficiency of professional prophylaxis on pigmentation reduction after the staining. There were built 71 specimens, divided in five groups,made of one direct composite resin (Tetric Ceram – Ivoclar/Vivadent – G1), three indirect composite resins (Targis – voclar/Vivadent – G2; Resilab Master – Wilcos – G3; belleGlass HP – Kerr – G4) and one porcelain (IPS Empress 2 – Ivoclar/Vivadent – G5), with the dimensions of 17 mm x 1mm. The specimens were immersed in staining media of coffee for 15 days, stored in controlled temperature of 37±1C at dark. In the sequency, they received a professional prophylaxis with sodium bicarbonate. The evaluations were made after 1, 7 e 15 days and after the prophylaxis, by means of reflectance spectrophotometry. Data were submitted to two-way ANOVA (p<0,001) and post-hoc tests with estathistical difference between G1 / G3 and the other groups; G2 / G4 and the other groups; and G5 and all the others. It was concluded that G1 e G3 showed the greatest color changes, lollowed by G2 and G4 and G5 showed the smallest changes. Professional prophylaxis was efficient to reduce the staining for all the materials tested.